Poziom wybranych zdolności motorycznych a komponentów składu ciała u dzieci trenujących piłkę nożną = The level of the selected motor skills and components of body composition in children football training - Krzysztof Byzdra; Oskar Jacyno; Janusz Mikołajczyk; Mirosław Piątek; Maria Kamrowska-Nowak; Robert Stępniak (Kazimierz Wielki University, 2015)
Byzdra Krzysztof, Jacyno Oskar, Mikołajczyk Janusz, Piątek Mirosław, Kamrowska-Nowak Maria, Stępniak Robert. Poziom wybranych zdolności motorycznych a komponentów składu ciała u dzieci trenujących piłkę nożną = The level of the selected motor skills and components of body composition in children football training. Journal of Education, Health and Sport. 2015;5(12):345-376. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35503 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A345-376 http://pbn.nauka.gov.pl/works/682661 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.11.2015. Revised 15.12.2015. Accepted: 17.12.2015.   POZIOM WYBRANYCH ZDOLNOŚCI MOTORYCZNYCH A KOMPONENTÓW SKŁADU CIAŁA U DZIECI TRENUJĄCYCH PIŁKĘ NOŻNĄ THE LEVEL OF THE SELECTED MOTOR SKILLS AND COMPONENTS OF BODY COMPOSITION IN CHILDREN FOOTBALL TRAINING   Krzysztof Byzdra, Oskar Jacyno, Janusz Mikołajczyk, Mirosław Piątek, Maria Kamrowska-Nowak AWFiS Gdańsk   Robert Stępniak UKW Bydgoszcz   Słowa kluczowe: zdolności motoryczne, skład ciała, dzieci, piłka nożna. Keywords: motor skills, body composition, children, football.   Streszczenie                 W pracy znajdują się cztery rozdziały teoretyczne. Pierwszy z nich podaje definicje motoryczności i podział zdolności motorycznych. Drugi mówi o sposobach pomiaru trzech głównych zdolności - siły, szybkości i wytrzymałości. Trzeci zawiera opis komponentów składu ciała oraz sposób ich pomiaru za pomocą aparatury firmy TANITA. Czwarty rozdział to opis rozwoju motorycznego i somatycznego dzieci i młodzieży szkolnej oraz momentów szczególnie ważnych dla rozwoju poszczególnych cech motorycznych.                 Celem pracy była ocena podstawowych wskaźników antropometrycznych (wzrost, masa ciała, BMI) dzieci trenujących piłkę nożną, na tle ogółu populacji dzieci w tym samym wieku oraz wyszukanie zależności między jakością składu ciała (ilość tkanki tłuszczowej, beztłuszczowej masy ciała, wody) a poziomem wydolności (wyrażonej w VO2max) i siłą mięśni nóg (wyrażoną w wysokości wyskoku oraz mocy).                 Badanie korelacji między wartościami komponentów składu ciała, a wynikami testów motorycznych wykazało że nie wszystkie zależności są istotne statystycznie, jednak wskazało te, w których zależność może być przedmiotem kolejnych analiz.   Abstract In the work, there are four theoretical chapters. The first of these gives the definitions of the motority and the distribution of motor skills. The second talks about how to measure three major abilities - strength, speed and endurance. The third contains a description of the components of body composition and the way in which they use measurement apparatus company TANITA. The fourth chapter is a description of the development of the child and the school children and youth physical and especially moments that are important for the development of individual characteristics. The aim of the work was to assess core anthropometric indicators (height, weight, BMI) children who regularly train in football, against the background of the general population of children of the same age and find the relationship between the quality of body composition (body fat, lean body mass, water) and capacity (expressed in VO2max) and the strength of the leg muscles (in the height of the jump, and power). Study of the correlation between the values of the components of body composition and motor test results performed.